1996
DOI: 10.1139/v96-036
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mapping of the active site of the glucoamylase ofAspergillus niger

Abstract: Abstract:A recently developed technique for the probing of the combining sites of lectins and antibodies, to establish the structure of the epitope that is involved in the binding of an oligosaccharide, is used to study the binding of methyl aisomaltoside by the enzyme glucoamylase. The procedure involved the determination of the effects on the kinetics of hydrolysis of both monodeoxygenation and mono-0-methylation at each of the seven hydroxyl groups in order to gain an estimate of the differential changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…This is analogous to the conformation found in studies of GA complexed with different inhibitors, 6-11 most structures making a hydrogen bond with Asp55 as maltosides do. 15,50 Both gt and tg conformations of the hydroxymethyl group are also possible and often lead to distinct clusters of docked structures, but they cause a molecular interaction energy penalty. The OH-6 A group is not only essential for hydrolysis of maltose and isomaltose, [50][51][52] but is equally necessary for the condensation of Dglucose and its deoxy derivatives.…”
Section: Docking Of Monosaccharide and Monosaccharide Analoguesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is analogous to the conformation found in studies of GA complexed with different inhibitors, 6-11 most structures making a hydrogen bond with Asp55 as maltosides do. 15,50 Both gt and tg conformations of the hydroxymethyl group are also possible and often lead to distinct clusters of docked structures, but they cause a molecular interaction energy penalty. The OH-6 A group is not only essential for hydrolysis of maltose and isomaltose, [50][51][52] but is equally necessary for the condensation of Dglucose and its deoxy derivatives.…”
Section: Docking Of Monosaccharide and Monosaccharide Analoguesmentioning
confidence: 99%
“…15,50 Both gt and tg conformations of the hydroxymethyl group are also possible and often lead to distinct clusters of docked structures, but they cause a molecular interaction energy penalty. The OH-6 A group is not only essential for hydrolysis of maltose and isomaltose, [50][51][52] but is equally necessary for the condensation of Dglucose and its deoxy derivatives. 3,53 The positional flexibility of this hydroxyl group in the GA active site could have some mechanistic implications both in substrate binding and in catalysis.…”
Section: Docking Of Monosaccharide and Monosaccharide Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…X100 GA catalytic domain obtained by X-ray crystallography in its native state or complexed with different inhibitors [8][9][10][11][12][13] was the basis for modeling the approximate interaction of GA with the substrates methyl a-maltoside and methyl a-isomaltoside in the first and second subsites. 14,15 The main interactions of these substrates with active-site residues and the catalytic water molecule were identified, with most of these residues being conserved in fungal, yeast, and bacterial GAs. 14,16,17 Automated docking with AutoDock, combining Monte Carlo methods with simulated annealing, has allowed the study of the interaction of proteins with small flexible molecules [18][19][20] and with other proteins.…”
Section: Introductionmentioning
confidence: 99%
“…niger GA activity ; Trp590 and Trp615 are responsible for starch granule adsorption (Svensson et al, 1986b). Studies with substrate analogues showed that the 3-, 4'-, and 6'-0H groups of maltosides as well as the 4-, 4'-, and 6'-0H groups of isomaltosides are required for rapid hydrolysis Pedersen, 1987, 1988;Bock et al, 1991;Lemieux et al, 1996).…”
Section: Chemical Modification Of Gamentioning
confidence: 99%